The Implementation of Communicative Media for Teaching English as a Foreign Language (EFL) during Pandemic of Covid-19 in Indonesian Senior High Schools - Reza Anis Maulidya; Nurmilah Fitria Atasyah; Nida Husna; Didin Nuruddin Hidayat; Farida Hamid (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The impact of Covid-19 outbreak in Indonesia compels the government to set urgent policies during the Covid-19 period. Therefore, the Ministry of Education and Culture had announced that schools have to continue carrying out teaching and learning activities virtually, which causes new problems to emerge; one of them is regarding inappropriate teaching media used by teachers. This study investigates the implementation of communicative teaching media in teaching English as a Foreign Language (EFL) during the pandemic in Indonesian senior high schools. As qualitative research, this study uses a literature study approach and questionnaire instrument to obtain data. Forth, the results show that social media dominate the implementation of communicative teaching media in Indonesia. English teachers' communicative media, which are frequently used, are WhatsApp then followed by Google Classroom and Zoom due to the simplicity in the technology used and features that adequately create collaborative, practical, active teaching and learning activities during the pandemic.